Brain dominance, gender, and specialty of education students of a Peruvian public university - Rojas Moscoso, Hernán Vicente (2022)
Objective: To determine if there is a relationship between quadrants A upper left brain, B lower left brain, C lower left limbic, and D upper right brain and the specialties and gender of education students at the Universidad Nacional Jorge Basadre Grohmann of Tacna. Material and methods: A sample of 229 students of both sexes was studied. The method used is the transversal-correlational descriptive. The brain dominance survey elaborated by Jiménez was applied. The data was processed by applying descriptive statistics. Inferential analysis with Student's T test, Chi-square test for homogeneity for two samples (male-female), and Snedocor's F (Anova). The processing was carried out with the SPSS 21 program. Results: The data analysis shows that there is no relationship between the brain quadrants and the specialty. The Mathematics, Computing, and Informatics students have greater dominance in the left hemisphere. Males present a higher mean score in the upper left cerebral quadrant A and females in the lower right limbal quadrant C; the former show significantly higher mean scores in the left hemisphere and the latter in the right hemisphere; however, the significance of this relationship is relatively low. Conclusion: There is a relationship between the brain quadrants and the specialty of the students of the School of Education, and there are differences in relation to gender.